NOTCH1 Is Aberrantly Activated in Chronic Lymphocytic Leukemia Hematopoietic Stem Cells - Di Ianni, Mauro; Baldoni, Stefano; Del Papa, Beatrice; Aureli, Patrizia; Dorillo, Erica; De Falco, Filomena; Albi, Elisa; Varasano, Emanuela; Di Tommaso, Ambra; Giancola, Raffaella; Accorsi, Patrizia; Rotta, Gianluca; et al. (Frontiers in Oncology, 2018)
To investigate Chronic Lymphocytic Leukemia (CLL)-initiating cells, we assessed NOTCH1 mutation/expression in hematopoietic stem cells (HSCs). In NOTCH1-mutated CLL, we detected subclonal mutations in 57% CD34+/CD38- HSCs. NOTCH1 mutation was present in 66% CD34+/CD38+ progenitor cells displaying an increased mutational burden compared to HSCs. Flow cytometric analysis revealed significantly higher NOTCH1 activation in CD34+/CD38- and CD34+/CD38+ cells from CLL patients, regardless NOTCH1 mutation compared to healthy donors. Activated NOTCH1 signaling resulted in overexpression of the NOTCH1 target c-MYC. We conclude that activated NOTCH1 signaling is an early event in CLL that may contribute to aberrant HSCs in this disease.